Comparison of consistency between wireless and conventional wired monitoring systems in gastrointestinal endoscopy - Peng Zhang; Jing Zhuang; Ting Li; Dan Fan; Qian Lei; Dayong Lin (Scientific Reports)
Abstract There is a lack of research on use and effectiveness of wearable monitoring devices in the setting of invasive procedures, such as gastrointestinal endoscopy. Our study aimed to compare the consistency between wireless and conventional wired monitoring systems in gastrointestinal endoscopy under sedation. One hundred and twenty patients undergoing gastrointestinal endoscopy with sedation/anesthesia were fitted with both wireless and conventional wired monitoring systems. Multiple physiological parameters, including heart rate (HR), pulse rate, peripheral oxygen saturation (SpO2) and systolic (SBP), diastolic (DBP) and mean blood pressure (MAP), were monitored and recorded simultaneously. The correlation coefficients were 0.999, 0.939, 0.606, 0.837, 0.934 and 0.941 for HR, pulse rate, SpO2, SBP, DBP and MAP, respectively (all p < 0.001). The HR exceeded its limits of agreements (LoAs) and clinically acceptable consistency thresholds in 56 (4.17%) and 41 (3.05%) data, pulse rate in 84 (6.0%) and 137 (9.80%) data, SpO2 in 116 (8.30%) and 18 (1.28%) data, SBP in 39 (6.32%) and 121 (19.61%)data, DBP in 34 (5.34%) and 52 (8.43%) data, and MAP in 28 (4.54%) and 57 (9.24%) data. The polar concordance rate at 30 degrees was 59.31% for SBP, 61.12% for DBP, and 68.55% for MAP according to polar plot trending analysis. This study demonstrated that the wireless monitoring system showed adequate agreement with wired system for HR and SpO₂, but suboptimal agreement for pulse rate, SBP, DBP, and MAP during gastrointestinal endoscopy. The blood pressure measurements meets the ISO 81060-2 accuracy criteria. Overall, wireless monitoring is generally acceptable for gastrointestinal endoscopy, but further validation is needed for high-risk patients.